Longitudinal stability of salivary microRNA biomarkers in children and adolescents with autism spectrum disorder. (July 2021) - Levitskiy, David; Confair, Alexandra; Wagner, Kayla E.; DeVita, Samantha; Shea, Nicole; McKernan, Elizabeth P.; Kopec, Justin; Russo, Natalie; Middleton, Frank A.; Hicks, Steven D.
Highlights: Saliva biomarkers that appear in early childhood are also present in adolescence. Early intervention affects expression of saliva RNAs in children with autism. Molecules in saliva hold promise as markers of therapeutic efficacy. Abstract: Background: Autism spectrum disorder (ASD) is a complex neurological condition with increasing prevalence. Few tools accurately predict the developmental trajectory of children with ASD. Such tools would allow clinicians to provide accurate prognoses and track the efficacy of therapeutic interventions. Salivary RNAs that reflect the genetic-environmental interactions underlying ASD may provide objective measures of symptom severity and developmental outcomes. This study investigated whether salivary RNAs previously identified in childhood ASD remain perturbed in older children. We also explored whether RNA candidates changed with therapeutic intervention. Method: A case-control design was used to characterize levels of 78 saliva RNA candidates among 96 children (48 ASD, 48 non-ASD, mean age: 11 years). Thirty-one children (22 ASD, 9 non-ASD developmental delay, mean age: 4 years) were followed longitudinally to explore changes of RNA candidates during early intervention. Saliva RNA and standardized behavioral assessments were collected for each participant. Associations between candidate RNAs and behavioral scores were determined in both groups via Spearman Correlation. Changes in candidate RNAs across two time-points were assessed in the younger cohort via Wilcoxon rank-sum test. Results: Seven RNAs were associated with VABS-II and BASC scores in the older group ([R] >0.25, FDR < 0.15). Within the younger cohort, 12 RNAs displayed significant changes over time (FDR < 0.05). Three microRNAs were associated with behavioral scores and changed over time (miR-182−5p, miR-146b-5p, miR-374a-5p). Conclusion: Several salivary RNAs are strongly associated with autistic behaviors in older individuals with ASD and change as early as three months after therapy initiation in younger children. These molecules could be used to track treatment effectiveness and provide prognoses. Further validation is necessary.